OC-047 New Platform for Trans-Anal Submucosal Endoscopic Resection- (TASER): Updated Clinical Results from Tertiary Centre. (17th August 2016) - Tsiamoulos, ZPP; Rameshshanker, R; Wawszczak, A; Warusavitarne, J; Saunders, BP
Abstract : Introduction: Current trans-anal surgical and advanced endoscopic resection procedures have the potential to resect complex rectal polyps (CRPs). However both approaches have limitations in terms of practicality and safety. Methods: Consecutive patients (Jan13/April15), referred for the excision of CRPs, were being considered for proctectomy and/or had failed conventional endoscopic/trans-anal therapy. The GelPoint Path trans-anal access port allowed dynamic tissue manipulation to facilitate endoscopic-submucosal-dissection/ESD. Supplementary techniques were also used: piecemeal-endoscopic-mucosal-resection or ablation/P-EMR or EMA and trans-anal excision/TAE. The aim of this study was to evaluate the feasibility, technical success and safety profile of this new hybrid, endo-surgical Trans-Anal Submucosal Endoscopic Resection- (TASER) approach for CRPs. Results: Thirty-two TASER procedures were employed in 31 patients (mean age 65 years/17 males-14 females) with 31 CRPs (mean size 8 cm/range 5 cm–18 cm). Complete endoscopic excision in a single session was achieved in 28/31 patients (93%); in one patient a second TASER session for completion of polypectomy, in another an elective laparoscopic-anterior-resection due to T1, sm3, N0, M0 and in a third patient a defunctioning-ileostomy due to intraperitoneal perforation before completion of polypectomy. Mean procedure time was 185 min, range 65–480 min. Thirty two TASER sessions were employed using ESD in 12/32, ESD+P-EMR in 6/32, ESD+P-EMR+EMA in 4/32, ESD+TAE in 3/32, ESD/P-EMR/TAE in 3/32 and ESD+P-EMR+EMA+TAE in 4/32. Intra-procedural bleeding was controlled with haemostatic endoscopic devices/surgical clipping. In 6/10 TASER-TAE cases there was a need for a full-thickness rectal dissection due to severe submucosal fibrosis: 4/6 cases were closed with surgical sutures/endoscopic clips and in 2/6 cases only endoscopic clips were deployed. Two episodes of delayed bleeding were reported with no transfusion/re-intervention requirement. All patients were discharged the day after the TASER apart from one patient who developed bacteremia requiring intravenous antibiotics/a 4 night hospital stay and the patient who required a defunctioning ileostomy, discharged on day 4 post-operation. First follow-up performed at 4–6 months interval in 25/31 patients showed: 21/25 with no recurrence/(84%) and 4/25/ (16%) with a minimal (<15mm) polyp recurrence, amenable to endoscopic therapy. No rectal stricturing was identified and only one episode of transient faecal incontinence were reported. Conclusion: TASER appears to be a safe and efficient endo-surgical approach providing an optimal platform for the minimally-invasive management of high- risk, complex rectal polyps. Disclosure of Interest: None Declared